Impact of a polyethylene liner on the storage of winter canola seed in unaerated steel bins - Moore, Kevin G.; Jones, Carol L. (Journal of stored products research, 2017)
Winter canola has potential as a rotational crop for small cereal grains throughout the southern United States. However, canola is typically harvested just before wheat and is not yet considered a primary crop in the south. This combined with already tight storage capacity has led producers and facility managers to look for ways to press older, low-quality storage bins into service. One idea has been the use of grain bag material as a liner for older bins that lack functional aeration systems. This project compared the storage quality of canola in lined and unlined steel grain bins without aeration. There was not a significant difference in storage quality between the lined and unlined bins. Canola seed at 5.4% moisture content was stored without loss in grade for eleven months. Lining the entire bin with grain bag material does not appear to be justified, however, there may be merit in lining the bottom of older grain storage bins to prevent moisture intrusion. •Comparison of canola seed quality in unaerated bins with and without grain bag liner.•No significant difference in storage quality between treatments.•Low moisture content seed stored eleven months with no grade reduction.•Potential use of grain bag liner in the bottom of bins to prevent moisture intrusion.